Evaluation of the Antioxidant Activity of the Fruiting Body of Phellinus linteus Using the On-line HPLC-DPPH Method - Jeon, Young Eun; Lee, Yeon Sil; Lim, Soon Sung; Kim, Sun-Ju; Jung, Sang Hoon; Bae, Young-Soo; Yi, Jae-Seon; Kang, Il-Jun (KOREAN SOC APPLIED BIOLOGICAL CHEMISTRY, 2009)
Phellinus linteus has traditionally been used as a medicinal mushroom in Oriental countries. Bioactive phytochemicals from the fruiting body of P. linteus were investigated using the on-line HPLC-DPPH system. The system was used to separate 10 antioxidants: protocatechuic acid (1) protocatechualdehyde, (2) caffeic acid (3), ellagic acid (4), hispidin (5), davalliallactone (6), interfungins A (7), hypholomine B (8), inoscavin A (9), and methyldavallialactone (10). Of these, compounds 6 and 7 showed the strongest inhibitory effect against the DPPH radical and superoxide anion radical-scavenging capacity. On comparison with quercetin (IC50 44.0 mu M), the IC50 value of compounds 6 and 7 for DPPH radical-scavenging capacity were 19.6 mu M and 18.5 mu M. Moreover, the antioxidative capacity of compound 6 at 40 mM was 2.95 nmol Trolox equivalents per mg dry wt. These results indicated that hispidin dimers such as hispidin with hispidin or hispolon had a stronger effect on radical-scavenging capacity than hispidin itself.
Keywords: RADICAL SCAVENGING COMPOUNDS; ALDOSE REDUCTASE; HISPIDIN; L.; CONSTITUENTS; INHIBITOR; CELLS